Voix over et peur au cinéma - Martin Barnier (Cahiers de Narratologie)
Voice over can be use to frighten movie audiences. From the film lecturer before 1914 to the 1970s Horror movies, voices accompanying images can create a gloomy atmosphere. Contrast between suspenseful images and a whispering voice can generate fear. With examples taken from Lang, Hitchcock, Tourneur, and unknown directors, we will show that voice over creates fear since a long tradition. But each time it evolves in a different way.